GSK3 Restrains Germinal Center B Cells to Form Plasma Cells - Lee, Jeonghyun; Park, Hyosung; Lim, Jiwon; Jin, Hyung-Seung; Park, Yoon; Jung, Yu-Jin; Ko, Hyun-Jeong; Yoon, Sung-Il; Lee, Geun-Shik; Kim, Pyeung-Hyeun; Choi, Sun Shim; Xiao, Changchun; et al. (AMER ASSOC IMMUNOLOGISTS, 2021)
B cells in the germinal center (GC) are programmed to form plasma cells (PCs) or memory B cells according to signals received by receptors that are translated to carry out appropriate activities of transcription factors. However, the precise mechanism underlying this process to complete the GC reaction is unclear. In this study, we show that both genetic ablation and pharmacological inhibition of glycogen synthase kinase 3 (GSK3) in GC B cells of mice facilitate the cell fate decision toward PC formation, accompanied by acquisition of dark zone B cell properties. Mechanistically, under stimulation with CD40L and IL-21, GSK3 inactivation synergistically induced the transcription factors Foxo1 and c-Myc, leading to increased levels of key transcription factors required for PC differentiation, including IRF4. This GSK3-mediated alteration of transcriptional factors in turn facilitated the dark zone transition and consequent PC fate commitment. Our study thus reveals the upstream master regulator responsible for interpreting external cues in GC B cells to form PCs mediated by key transcription factors.
Keywords: FOLLICULAR HELPER-CELLS; TRANSCRIPTION FACTOR; C-MYC; CENTER LIGHT; RECEPTOR; GENE; SELECTION; DIFFERENTIATION; PROLIFERATION; BACH2